Monogenic Autoinflammatory Syndromes: State of the Art on Genetic, Clinical, and Therapeutic Issues. (24th October 2013) - Caso, Francesco; Rigante, Donato; Vitale, Antonio; Lucherini, Orso Maria; Costa, Luisa; Atteno, Mariangela; Compagnone, Adele; Caso, Paolo; Frediani, Bruno; Galeazzi, Mauro; Punzi, Leonardo; Cantarini, Luca
Abstract : Monogenic autoinflammatory syndromes (MAISs) are caused by innate immune system dysregulation leading to aberrant inflammasome activation and episodes of fever and involvement of skin, serous membranes, eyes, joints, gastrointestinal tract, and nervous system, predominantly with a childhood onset. To date, there are twelve known MAISs: familial Mediterranean fever, tumor necrosis factor receptor-associated periodic syndrome, familial cold urticaria syndrome, Muckle-Wells syndrome, CINCA syndrome, mevalonate kinase deficiency, NLRP12-associated autoinflammatory disorder, Blau syndrome, early-onset sarcoidosis, PAPA syndrome, Majeed syndrome, and deficiency of the interleukin-1 receptor antagonist. Each of these conditions may manifest itself with more or less severe inflammatory symptoms of variable duration and frequency, associated with findings of increased inflammatory parameters in laboratory investigation. The purpose of this paper is to describe the main genetic, clinical, and therapeutic aspects of MAISs and their most recent classification with the ultimate goal of increasing awareness of autoinflammation among various internal medicine specialists.